Design of interfaces with lithographically patterned adhesive pads for gluing at the microscale. (October 2018) - Samyn, Pieter; Rühe, Jürgen; Prucker, Oswald; Biesalski, Markus
Abstract: The creation of small adhesive pads by traditional dispensing methods is technically limited. However, the miniaturisation of micromechanical components requires the parallel development of adhesive pads with sizes in the sub-50 µm range combining good geometrical confinement and mechanical strength. Therefore, a new design of interfaces with adhesive pads of 32–8 µm are presented through local deposition of a liquid adhesive by means of "top-down" or "bottom-up" patterning. Using lithography and photochemical process, the shape of the adhesive pads is first stabilized by partial cross-linking and effective adhesive bonding with a counterface subsequently takes place during full cross-linking. The parameters for photochemical cross-linking of the adhesive pads are optimised and the mechanical performance of the patterned adhesive interfaces is evaluated. For "top-down" patterned adhesive interfaces, the geometrical stabilisation of the adhesive pads requires relatively long cross-linking times consequently resulting in low mechanical strength. For "bottom-up" patterned adhesive interfaces, the formation of adhesive pads is controlled by self-organisation of the adhesive over chemically structured substrates and requires short cross-linking times for geometrical stabilization, leading to higher mechanical strength during adhesive bonding. The fabrication of adhesive pads by a "bottom-up" approach is further discussed in relation to the influences of processing parameters on dewetting of the adhesive.